A Sensitivity Study of the Mathematical Model for Carbon Dioxide Removal by Physical Absorption in the Production of Biomethane from Palm Empty Fruit Bunch - Mohd Asrul, Mohamad Afiq; Abdul Halim Yun, Hafizah; Atan, Mohd Farid; Tan Ai Wei, Ivy; Lai Chang Hui, Josephine (International Journal of Integrated Engineering, 2024)
A non-equilibrium rate-based absorption model based on the two-film theory was adapted for the physical solvent in a packed bed column with co-counter current flow in place of chemical reaction. Carbon dioxide (CO2) removal from fresh biomethane in a palm empty fruit bunch thermochemical conversion plant to improve the purity of the dried gas was modeled from the approximation of mathematical equations. This objective was achieved by improvising and reducing the model assumptions with guaranteed accuracy based on the validation using the established measured data. A better mathematical model with the predicted temperature profile at the liquid side and a mean absolute percentage error of less than 25% contributed to the 2 wt.% differences between the assumed dimethyl ether polyethylene glycol purity and the experiment, which is sufficient to be considered acceptable. To understand the performance of the absorption column, the sensitivity of three input variables on the removal of CO2 was analyzed, including the temperature, pressure, and solvent feed flow rate by manipulating the input value for each variable individually. The optimum temperature of 31 °C, pressure of 1.6 kPa, and solvent feed flow rate of 1:1 liquid-to-gas ratio were established as the baseline values for the sensitivity test. The analysis from the mathematical model indicates a significant influence of the operating temperature on CO2 absorption. This study enhances biomethane purity, optimizes CO2 removal, and improves operational efficiency. It aligns with sustainability goals, reduces emissions, and offers economic benefits, making it valuable for the renewable energy industry.